The Role of Social Media in EFL Vocabulary Development in University - I Made Sofyan T; Mochtar Marhum; Sukmawati Sadiilia; Agussatriana Agussatriana (Universitas Pahlawan Tuanku Tambusai, 2026)
This study explored the role of social media in enhancing EFL students’ vocabulary development at Tadulako University. It addressed the limited research on students’ experiences using social media for vocabulary learning in the Indonesian university context. A qualitative descriptive design was employed involving three students from the English Education Study Program. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed that platforms such as Instagram and TikTok supported vocabulary development by providing authentic language exposure through videos, captions, comments, and online interactions. Students also benefited from contextual learning, repeated exposure, multimedia content, and social interaction, which increased their motivation and engagement in learning English vocabulary. Nevertheless, they encountered several challenges, including fast speech, slang expressions, distractions, and limited subtitle availability. Overall, social media functioned as an effective informal digital learning environment that facilitated vocabulary acquisition beyond the classroom. These findings suggest that educators should integrate social media into vocabulary instruction to complement formal learning while guiding students in overcoming potential challenges and maximizing its educational benefits.